The Impact Of Multiplication Board Learning Innovation On The Multiplication Skills Of Third-Grade Elementary School Students - Purwandini, Alyana Putri Eka; Siwanto, M.Bambang Edi (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2026)
The ability to perform multiplication operations is one of the main foundations of mathematics learning in elementary school. However, many students still experience difficulties in understanding and mastering multiplication. This obstacle not only affects their low mathematics scores but also hinders their ability to solve more challenging problems at the next level. This study aims to examine the effectiveness of the Multiplication Board learning media innovation in improving the multiplication skills of third-grade elementary school students. The method used is experimental research with a Pretest-Posttest Control Group Design. The results of the study show a significant improvement. The conclusion of this study is that the Multiplication Board is effective in supporting mathematics learning, especially multiplication material, because it has been proven to improve students' calculation skills. Kemampuan mengerjakan operasi perkalian merupakan salah satu landasan utama dalam pembelajaran matematika di sekolah dasar. Meski begitu, masih banyak peserta didik yang mengalami hambatan dalam memahami serta menguasai perkalian. Kendala ini tidak hanya berpengaruh pada rendahnya nilai matematika, tetapi juga mengganggu kemampuan mereka ketika menghadapi soal-soal yang lebih menantang pada jenjang berikutnya. Penelitian ini bertujuan untuk menguji efektivitas inovasi media pembelajajan Papan Perkalian dalam meningkatkan kemampuan berhitung perkalian siswa kelas III Sekolah Dasar. Metode yang digunakan adalah penelitian eksperimen dengan desain Pretest-Posttest Control Group Design. Hasil penelitian menunjukkan adanya peningkatan signifikan. Kesimpulan penelitian ini adalah Papan Perkalian efektif dalam menunjang pembelajaran matematika, khususnya materi perkalian, karena terbukti mampu meningkatkan kemampuan berhitung siswa.